Peran kesehatan guru dan lingkungan kerja terhadap kinerja guru melalui prestasi kerja pada guru Sekolah Dasar di Cilegon - Fatimah, Fatimah; Yusuf, Furtasan Ali; Hayadi, Herawan; Suparmoko, Muhamad; Sari, Gema Ika; Muafidah, Muafidah (Universitas Muhammadiyah Magelang, 2024)
Teacher performance is a key factor in achieving optimal quality education. This research aims to investigate the influence of organizational learning and discipline on teacher performance, with work performance as a mediating variable, among elementary school teachers in Cilegon City. This research uses a quantitative approach with a survey method. The research sample consisted of 200 elementary school teachers selected randomly. Data collection is carried out through questionnaires that measure organizational learning, discipline, work performance and teacher performance. Data analysis was carried out using path analysis techniques to test the direct and indirect relationships between these variables. The research results show that organizational learning and discipline have a significant positive effect on teacher work performance. In addition, job performance is proven to be a significant mediator in the relationship between organizational learning and discipline on teacher performance. These findings indicate that improving teacher performance can be achieved by developing an organizational learning culture and strengthening discipline. Job performance plays an important role in strengthening the impact of these two factors on teacher performance. Organizational learning and discipline are important factors that influence teacher performance, with job performance as a significant mediator. Implementation of policies that support organizational learning and discipline can improve teacher performance in elementary schools in Cilegon City